Blood Gene Expression Reveal Pathway Differences Between Diet‐Sensitive and Resistant Obese Subjects Prior to Caloric Restriction - Ghosh, Sujoy; Dent, Robert; Harper, Mary E.; Stuart, Joan; McPherson, Ruth (Obesity (Silver Spring, Md.), 2011)
Weight loss in response to caloric restriction displays significant interindividual heterogeneity. To develop early predictors of weight‐loss success, we have compared whole‐blood gene expression profiles of obese, diet‐sensitive vs. obese, diet‐resistant subjects prior to the initiation of clinically supervised caloric restriction. Pathway enrichment analysis of gene expression profiles by multiple applications converged on the “oxidative phosphorylation” (OXPHOS) pathway, and to a lesser extent the “proteasome” pathway, as statistically significantly upregulated in obese, diet‐sensitive subjects compared to the diet‐resistant subjects. The finding of increased OXPHOS is consistent with earlier observations of increased proton leak, increased expression of OXPHOS genes, and increased oxidative muscle fibers in skeletal muscle of obese, diet‐sensitive subjects. The current study further highlights the utility of blood as a sentinel tissue reflecting systemic states and provides a potential modality to predict future weight‐loss success, relevant to the design of individualized bariatric treatment programs.